Midge‐stabilized sediment drives the composition of benthic cladoceran communities in Lake Mývatn, Iceland. Issue 2 (10th February 2017) - Webert, Kyle C.; Herren, Cristina M.; Einarsson, Árni; Bartrons, Mireia; Hauptfleisch, Ulf; Ives, Anthony R.
Abstract: The importance of environmental disturbances as drivers of ecological communities depends not only on the magnitude of the disturbance, but also on the disturbance‐specific sensitivity of the community. Organisms that alter the physical structure of their surroundings can affect the sensitivity of their habitat to environmental disturbance, and may alter the potential for disturbance to shape ecological communities. Such organisms therefore act as ecosystem engineers by indirectly modifying the resources available to other species. The benthos of shallow, eutrophic Lake Mývatn, Iceland, is frequently disturbed by wind events that lead to sediment resuspension. The impact of wind, however, depends on the abundance of midges (Chironomidae) whose larval tubes bind sediment and reduce wind‐driven resuspension. Here, we investigate the long‐term effect of fluctuations in midge abundance on the benthic cladoceran community using two lake sediment cores representing 30 and 140 years of deposition. In both cores, midge remains show a significant positive correlation with abundance of a large benthic surface‐dwelling cladoceran, Eurycercus lamellatus, relative to the abundance of a small within‐sediment‐dwelling cladoceran, Alona rectangula . To experimentally investigate whether this shift could have been caused by midges acting as ecosystem engineers, we subjected cladoceran communities to sediment resuspension events within mesocosms. We found a significant decrease in abundance of the large epibenthic E. lamellatus relative to the abundance of small infaunal Alona spp. when subjected to disturbance. These findings show that physical alteration of benthic sediment and hence the sensitivity of the sediment to disturbance may explain the community shift in cladocerans observed with fluctuating midge abundance in Lake Mývatn.